2014
DOI: 10.1152/ajpheart.00422.2013
|View full text |Cite
|
Sign up to set email alerts
|

Systemic vascular effects of acute electrical baroreflex stimulation

Abstract: Burgoyne S, Georgakopoulos D, Belenkie I, Tyberg JV. Systemic vascular effects of acute electrical baroreflex stimulation. Am J Physiol Heart Circ Physiol 307: H236 -H241, 2014. First published May 9, 2014; doi:10.1152/ajpheart.00422.2013.-We intended to determine if acute baroreflex activation therapy (BAT) increases venous capacitance and aortic conductance. BAT is effective in resistant hypertension, but its effect on the systemic vasculature is poorly understood. Left ventricular (LV) and aortic pressures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…23,24 Our data demonstrate that the acute BP decrease during BAT is mainly achieved by changes in the vasculature and not so much to the heart. A recent study by Burgoyne et al 25 demonstrated an increase in arterial conductance and venous capacitance with acute BAT, which is consistent with our results and is consistent with the view that a drop in sympathetic activity is responsible for the cardiovascular effects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…23,24 Our data demonstrate that the acute BP decrease during BAT is mainly achieved by changes in the vasculature and not so much to the heart. A recent study by Burgoyne et al 25 demonstrated an increase in arterial conductance and venous capacitance with acute BAT, which is consistent with our results and is consistent with the view that a drop in sympathetic activity is responsible for the cardiovascular effects.…”
Section: Discussionsupporting
confidence: 93%
“…23,24 Estos datos demuestran que la disminución aguda de la PA durante el BAT se logra principalmente mediante cambios en la vasculatura y no tanto en el corazón. Un estudio reciente realizado por Burgoyne et al 25 demostró un aumento de la conductividad arterial y capacidad venosa con el BAT agudo, lo que concuerda con nuestros resultados y con la perspectiva de que la disminución de la actividad simpática es responsable de los efectos cardiovasculares.…”
Section: Discussionunclassified
“…It was thus hypothesized that the sympathoinhibition triggered by the stimulation of carotid baroreceptors would lead to an improvement in arterial function. However, at variance from what already reported in animal models of heart failure [22,23], no significant improvement of carotid-femoral pulse wave velocity and augmentation index, calculated from central blood pressure analysis, was observed following a 3-month follow-up [27]. These findings are in contrast with the evidence collected in resistant hypertensive patients demonstrating a favorable effect of the baroreflex activation therapy on the main functional features of the large arteries [28•], which have been shown to be under sympathetic and reflex influences [29,30].…”
Section: Pilot Studies In Congestive Heart Failure Patientsmentioning
confidence: 74%
“…Acutely, carotid baroreceptor stimulation in healthy dogs significantly increases stroke volume and reduces heart rate while preserving cardiac output as well as renal perfusion [21,22]. This is achieved by reducing systemic vascular resistance and arterial stiffness [23]. The reduced myocardial oxygen demand, the increased cardiac reserve, as well as the preserved tissue perfusion allow to improve functional capacity and protect against the arrhythmogenic effects of myocardial ischemia.…”
Section: Studies In Experimental Models Of Heart Failurementioning
confidence: 99%
See 1 more Smart Citation